The faraway nearby - Solnit, Rebecca (Viking, 2013)
A companion to "A Field Guide for Getting Lost" explores the ways that people construct lives from stories and connect to each other through empathy, narrative, and imagination, sharing anecdotes about historical figures and members of the author's own family.